Efektivitas Lembar Kerja Siswa Virtual Laboratory pada Materi Gerak Lengkung di Kelas X SMAN - Hidayati Hidayati; Masril Masril; Yenni Darvina; Zara Zakiya (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The purpose of this study was to determine the effectiveness of virtual laboratory worksheets on parabolic motion material and circular motion in class X of SMAN 5 Padang. To achieve the research objectives, quasi experiments were used and one group of pretest-posttest was research design. The population is students of class X MIPA at SMAN 5 Padang who are registered in the 2018/2019 Academic Year. Simple random sampling technique is used for sampling and obtained by class X MIPA 1 as a sample. The research data includes data on attitudes, knowledge and skills competencies. Attitude competency data is obtained through attitude assessment observation sheets, then described and analyzed in graphical form. Knowledge competency data was obtained through pretest and posttest. Skills competency data are obtained through performance assessment sheets. Knowledge and skills competency data were analyzed using correlated t-test. Based on data analysis, it can be concluded that virtual laboratory worksheets on parabolic motion material and circular motion are effectively used in learning which can be seen from increasing student learning competencies in aspects of knowledge and skills after using virtual laboratory worksheets. As well as attitudinal competence shows students have done a very good attitude during learning, marked by an increase in the average value of student attitudes at each meeting